2018
DOI: 10.1021/acs.macromol.8b02121
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinarily Large LCST Depression Converts Nonthermosensitive Polymer to Thermosensitive

Abstract: A facile method to tune the phase transition temperature of thermosensitive polymers is to introduce an additive; however, the influence of additives is usually limited. Here the influence of poly­(vinyl alcohol) (PVA), a polymeric additive, on thermal behavior of copolymers of acrylamide (AAm), N,N-dimethyl­acrylamide (DMAA), and 3-(acrylamido)­phenyl­boronic acid (3-AAPBA), P­(AAm-DMAA-3-AAPBA), was studied. With increasing AAm content, the phase transition temperature of the copolymers increases gradually. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Proteins vary hydrophobic/hydrophilic interactions, leading to variations in LCST, size ( d H ), and conformational state of the copolymer. A slight discrepancy in LCST was observed for results obtained from thermal fluorescence and DLS measurements, which can be different operational methods for these biophysical techniques. ,, Nonetheless, both techniques give a similar trend in the variation of LCST. The corresponding standard deviations obtained from d H values, LCST values obtained from temperature-dependent fluorescence, and DLS are illustrated in Table S1–S3.…”
Section: Resultsmentioning
confidence: 86%
“…Proteins vary hydrophobic/hydrophilic interactions, leading to variations in LCST, size ( d H ), and conformational state of the copolymer. A slight discrepancy in LCST was observed for results obtained from thermal fluorescence and DLS measurements, which can be different operational methods for these biophysical techniques. ,, Nonetheless, both techniques give a similar trend in the variation of LCST. The corresponding standard deviations obtained from d H values, LCST values obtained from temperature-dependent fluorescence, and DLS are illustrated in Table S1–S3.…”
Section: Resultsmentioning
confidence: 86%
“…Thus, we conducted the sequential block copolymerization of PBnGE, followed by EGE, using the t-Bu-P 4 /tBBA system with [BnGE] 0 /[EGE] 0 /[tBBA] 0 ratios of 10/90/1, 20/80/1, 30/70/1, 40/60/1, and 50/50/1 to afford a series of PBnGE x -b-PEGE y with various x and y values (Scheme 1 and Table 1). As the first step of block copolymerization, t-Bu-P 4 with a [BnGE] 0 /[tBBA] 0 /[t-Bu-P 4 ] 0 ratio of 50/1/1 catalyzed ROP of BnGE for 20 h. 1 H NMR and SEC analysis of aliquots of the polymer showed that the monomer conversion rate reached 99%, and it was verified that active PBnGE oxyanions were formed, with an M n, NMR value of 8.3 kg mol −1 and M w /M n of 1.04. Then, the block copolymerization second stage was started by adding 50 equivalents of EGE relative to the tBBA used for the first polymerization.…”
Section: Synthesis Of Statistic Copolymers and Block Copolymersmentioning
confidence: 99%
“…Aqueous solutions of some polymers show reversible phase-transition behavior, such as white turbidity when heated above the lower critical solution temperature (LCST) and dissolving again to clear when cooled below the LCST [1][2][3]. Such polymers include poly (N-substituted acrylamide)), poly (N-substituted methacrylamide), polyethers, and methyl cellulose [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Copolymerization has been utilized to create new TRPs from non‐responsive substrates. [ 27 ] Homopolymers of acrylamide (AAm) are freely soluble in water, but copolymers of AAm with hydrophobic comonomers such as acrylonitrile, azobenzene, diaminopyridine, or styrene can have a UCST in aqueous solutions. [ 28–31 ] In contrast, homopolymers of dimethyl acrylamide (DMA) is also water‐soluble, but copolymer of DMA with hydrophobic monomers, such as styrene or phenylacrylamide, exhibit LCST behavior in water.…”
Section: Methodsmentioning
confidence: 99%